Cortical preparatory activity: representation of movement or first cog in a dynamical machine? - Churchland, MM (2010)
The motor cortices are active during both movement and movement preparation. A common assumption is that preparatory activity constitutes a sub-threshold form of movement activity: a neuron active during rightwards movements becomes modestly active during preparation of a rightwards movement. We asked whether this pattern of activity is in fact observed. We found that it was not: at the level of a single neuron, preparatory tuning was weakly correlated with movement-period tuning. Yet somewhat paradoxically, preparatory tuning could be captured by a preferred direction in an abstract ‘space’ that described the population-level pattern of movement activity. In fact, this relationship accounted for preparatory responses better than did traditional tuning models. These results are expected if preparatory activity provides the initial state of a dynamical system whose evolution produces movement activity. Our results thus suggest that preparatory activity may not represent specific factors, and may instead play a more mechanistic role.